ANALISIS KESALAHAN VERBA KUDASAIMASU DAN ITADAKIMASU PADA MAHASISWA PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU ANGKATAN 2015 TAHUN AJARAN 2017/2018 - Ahmad Muji Sholihin; Hadriana Hadriana; Zuli Laili Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is a research about the analysis of verb error kudasaimasu and itadakimasu by the class 2015 students of Japanese Language Education Study Program University of Riau academic year 2017/2018. The purpose of this research is to measure students understanding of the use of verb kudasaimasu and itadakimau. Then, to know the difficulty factor in understanding the use of these two verbs. This research used quantitative descriptive method by using survey as the research design. The data were obtained by using test and questionnaire by the respondents. This research was done as a quantitative research in the field of education. All data processed using statistic method and the result converted by descriptive method to describe the result. Based on the results of the test, it can be seen that the average value of the use of these verbs is 53,2 . The test results show that the highest score is 76 and the lowest score is 36. It’s mean that students still often make error to use it in conversation and answer questions. It is supported by the questionnaire result that students experience containts in using verb kudasaimasu and itadakimasu. According to the questionnaire results, the factors causing difficulties are some students still do less exercise and repetition of verb kudasaimasu and itadakimasu so that student’s memory of the use of this verb be decline.Keywords : verb errors,kudasaimasu, itadakimasu